ASSESSING THE CHEMICAL PROPERTIES OF DAMMAR ASPHALT USING FOURIER TRANSFORM INFRARED SPECTROSCOPY - Ary Setyawan; M Fachri; A Sumarsono (ALCHEMY Jurnal Penelitian Kimia, 2016)
Dammar Asphalt (Daspal) is expected to be used as a bio-asphalt renewable binder for road construction. It is made with a modification of the "Jabung", which is the dammar gum based material mixed with grounded red brick debris and low quality cooking oil at a certain ratio. Dammar gum is obtained from the Dipterocarpaceae family of trees in India and East Asia, most are produced by tapping trees. The gum varies in color from clear to pale yellow. Dammar gum is a triterpenoid resin, containing a large number of triterpenes and their oxidation products. Many of them are low molecular weight compounds. The objective of this research is to analyze the chemical properties of Daspal uses a Resonance Fourier Transform Infrared Spectroscopy (FTIR) method to compare with conventional asphalt. The investigation using spectral data showed that all types of Daspal have similar functional groups of Saturate, Aromatic, Resins, and Asphalten as the 60/70 penetration conventional bitumen, so that based on its chemical properties Daspal can be considered as bioaspal.